Perceptions of cocoa growers in Malaysia on relationship between transfer of technology skills, human resource development skills and extension agents’ work performance - Oluwatoyin, Olagunju (2019)
This study was designed to determine extension agents’ transfer of technology skills and human resource development skills that explain work performance based on cocoa growers perceptions in Malaysia. Specifically, the study were conducted to; (i) determined extension agents’ level of technology transfer skills, human resource development skills and work performance as perceived by cocoa growers, (ii) determine the relationship between transfer of technology skills, human resource development skills and extension agents’ work performance, (iii) identify the most important factors contributing to work performance of the extension agents. Data for the study were solicited from 1122 productive cocoa growers through self administered questionnaire by using Krejcie and Morgan formula. They were selected through stratified sampling method from a total population of 1902 in the three (3) regions of cocoa smallholders in Malaysia: Peninsular Malaysia, Sabah and Sarawak. The data were analyzed using descriptive statistics, Pearson correlation and multiple regression analysis. Results indicated that nearly all cocoa growers rated their level of work performance as high. A majority of respondents also rated their transfer of technology skills on technical skill, technology delivery skill and technology evaluation skill as high. Furthermore, majority of the respondents also indicated high ratings for human resource development skills on leadership skill, decision making support skill and social skill. The finding supported the positive and moderate relationship between all transfer of technology skills, human resource development skills and work performance. However, five skills were significant in explaining work performance of extension agents’. These are technical skill, technology delivery skill, leadership skill, decision making support skill and social skill. In addition, transfer of technology skills and human resource development skills predicts work performance of extension agents’ as perceived by cocoa growers, but the contribution is higher in human resource development skills component. The study is important as it contributes to Resource Based Theory and Human Capital Theory by strengthening intangible resources (skills) regarding high performance and emphasizing the role of workers’ experience which was ignore by initial research which focuses on education and training for productivity and improved performance. Also, it confirmed core and specialized skills that extension agents need to have in both technical and human development for effective extension service delivery. The findings would also assist policy makers and MCB management in increasing the performance of extension agents through training and development on technology transfer skills and human resource development skills with support from top management and middle level staff. The skills that have been identified in this study can be integrated into both the preservice and in-service training and development of extension agents. The combination of transfer of technology skills and human resource development skills is very important to be considered by the relevant agencies in order to improve extension agents’ capabilities and performance. The study recommends that further studies should be conducted on other variables that help determine extension agents’ work performance. Also, MCB and other agricultural extension service agencies should focus more attention on delivering consistent technology and human resource development initiatives relevant to the need of extension agents and focused on addressing identified skills, knowledge and abilities gaps for a continuous performance improvement in their work.